Moving particle semi-implicit method : a meshfree particle method for fluid dynamics /: a meshfree particle method for fluid dynamics. (2018) - Koshizuka, S; Shibata, Kazuya; Kondō, Masahiro; Matsunaga, Takuya
No abstract available